Mempertimbangkan Spiritualitas Ekonomi Berdasarkan Intuisi Kosmotheandrik Raimundo Panikkar - Yan Okhtavianus Kalampung (Gema Teologika, 2018)
This essay going to argue that Raimundo Panikkar's concept of Cosmotheandric Intuition has strong significance in forming an economics spirituality. Economics system nowadays tend to become a system of greediness. By considering cosmology concept such as cosmotheandric intuition and its significant relation, writer made a counter spirituality to all of negative effect of capitalism economics. At the first part of this paper will briefly explain about Raimundo Panikkar and his proposal of Cosmotheandric Intuition. After showing problems in contemporary economics discourse, this paper explain the meaning of spirituality, as a basis understanding to form an economics spirituality. At the part of analysis about economics spirituality, writer wrote counter arguments to capitalist economics system based on Cosmotheandric Intuition. Therefore writer find it usefull to form an economics spirituality based on it.